Pendekatan Partisipatif dalam Pemberdayaan UMKM: Studi Kasus Inovasi Jellybone dari Limbah Tulang Ikan - Hartoni, Hartoni; Sari, Dwi Inda; Melki, Melki; Ningsih, Ellis Nurjualisti; Febrianti, Amanda Astri Pratiwi; Isnaini, Isnaini; Pramudhya, Rizqy (Abdimas Mandalika, 2026)
Abstract:  This community service program aims to empower MSMEs in Tanjung Batu Seberang Village, Ogan Ilir Regency, by utilizing fish bone waste into a high-value-added product called Jellybone. The approach used was Participatory Rural Appraisal (PRA) with an action research method over 1 months. The program included integrated training (production, business management, and marketing), application of appropriate technology, intensive mentoring, and institutional development. The results showed a significant increase in partners' capacity, with an average increase of 43.3% in understanding based on pre-test and post-test results. The establishment of the Joint Business Group (KUB) "Jellybone Mandiri" and a branding transformation formed the foundation for business sustainability. The program created multidimensional impacts, including increased income, reduction of fish bone waste by up to 70%, and strengthened social capital, aligning with the principles of the circular economy and the Sustainable Development Goals (SDGs).Abstrak: Program pengabdian masyarakat ini bertujuan untuk memberdayakan UMKM di Desa Tanjung Batu Seberang, Kabupaten Ogan Ilir, melalui pemanfaatan limbah tulang ikan menjadi produk bernilai tambah tinggi, yaitu Jellybone. Pendekatan yang digunakan adalah participatory rural appraisal (PRA) dengan metode action research selama 1 bulan. Program ini mencakup pelatihan terintegrasi (produksi, manajemen usaha, dan pemasaran), penerapan teknologi tepat guna, pendampingan intensif, dan pembentukan kelembagaan. Hasilnya menunjukkan peningkatan signifikan kapasitas mitra, dengan rata-rata peningkatan pemahaman sebesar 43,3% berdasarkan hasil pre-test dan post-test. Terbentuknya Kelompok Usaha Bersama (KUB) "Jellybone Mandiri" serta transformasi branding menjadi fondasi keberlanjutan usaha. Program ini memberikan dampak multidimensi, meliputi peningkatan pendapatan, pengurangan limbah tulang ikan hingga 70%, dan penguatan modal sosial, yang sejalan dengan prinsip ekonomi sirkular dan Tujuan Pembangunan Berkelanjutan (SDGs).